FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN KEPUTIHAN PADA WANITA USIA SUBUR - Sipayung, Helmi Rosdelina; Yuliasari, Dewi; Anggraini, Anggraini; Suharman, Suharman (Sekolah Tinggi Ilmu Kesehatan Adila Bandar Lampung, 2026)
Background: Vaginal discharge (flour albus) is a common reproductive problem in women of childbearing age (WUS) that can be physiological or pathological. In Indonesia, up to 90% of women experience it, mainly due to the tropical climate, poor genital hygiene, and fungal, bacterial or parasitic infections such as Candida and Trichomonas vaginalis. The impact includes infertility, anxiety, and even cervical cancer. Pre-survey data at Puskesmas Kedondong showed that all WUS had never received related education, 88% had poor personal hygiene behavior, and 28% experienced pathological vaginal discharge. The causative factors include knowledge, attitude, hygiene behavior, age, education, and menstrual cycle. Purpose: The purpose of the study was to determine the factors associated with the incidence of vaginal discharge in women of childbearing age in the Kedondong Health Center Working Area. Methods : This type of research is quantitative, cross sectional research design. The population in this study were all women of childbearing age (WUS) aged 15-49 years in the Kedondong Health Center Working Area as many as 6317 respondents with a sample of 377 WUS using proportional random sampling technique. Data collection using questionnaire sheets, univariate and bivariate data analysis (chisquare test). Results: The results of the univariate study found that as many as 207 (54.9%) respondents with good knowledge, as many as 203 (53.8%) respondents with a positive attitude, as many as 260 (69.0%) respondents with positive hygiene behavior, and as many as 267 (70.8%) respondents experienced normal vaginal discharge. Conclusion: There was a relationship between knowledge (p-value = 0.001), attitude (p-value = 0.001), personal hygiene behavior (p-value = 0.001) with the incidence of vaginal discharge in women of childbearing age in the Kedondong Health Center Working Area. Suggestion: Advice for health workers can provide counseling on vaginal discharge prevention to improve the reproductive health of women of childbearing age.